Strategi Tim Kreatif Nusantara TV Dalam Meningkatkan Eksistensi Program Kok Bisa Viral - Dewi, Yemima Agnes Lolita; Wulandari, Yulianti Fajar; Himawan, Sultan (Prisani Cendekia Institute, 2024)
In the era of globalization with the advancement of technology such as television, many televisions compete to present programs that are entertaining yet informative and educational. Kok Bisa Viral is a program that is present on Nusantara TV station which is a semi-national television. The challenge of increasing the existence of the program arises for the creative team in the midst of various programs from other television stations. This research was conducted to find out the Strategy of Nusantara TV Creative Team in Improving the Existence of Kok Bisa Viral Program. The research used a qualitative method with a descriptive approach and the theory used was Lasswell's communication theory. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study found that the creative team's strategy in improving the existence of the Kok Bisa Viral program is program planning, determining the target audience, program implementation, and strategies to improve program existence.